Transcriptomics and systems biology analysis in identification of specific pathways involved in cacao resistance and susceptibility to witches' broom disease - Hora Junior, Braz Tavares da; Poloni, Joice de Faria; Lopes, Maiza Alves; Dias, Cristiano Villela; Gramacho, Karina Peres; Schuster, Ivan; Sabau, Xavier; Cascardo, Julio Cezar de Mattos; Zingaretti Di Mauro, Sonia Marli [UNESP]; Gesteira, Abelmon da Silva; Bonatto, Diego; Micheli, Fabienne (Royal Soc Chemistry, 2012)
This study reports on expression analysis associated with molecular systems biology of cacao-Moniliophthora perniciosa interaction. Gene expression data were obtained for two cacao genotypes (TSH1188, resistant; Catongo, susceptible) challenged or not with the fungus M. perniciosa and collected at three time points through disease. Using expression analysis, we identified 154 and 227 genes that are differentially expressed in TSH1188 and Catongo, respectively. The expression of some of these genes was confirmed by RT-qPCR. Physical protein-protein interaction (PPPI) networks of Arabidopsis thaliana orthologous proteins corresponding to resistant and susceptible interactions were obtained followed by cluster and gene ontology analyses. The integrated analysis of gene expression and systems biology allowed designing a general scheme of major mechanisms associated with witches' broom disease resistance/susceptibility. In this sense, the TSH1188 cultivar shows strong production of ROS and elicitors at the beginning of the interaction with M. perniciosa followed by resistance signal propagation and ROS detoxification. on the other hand, the Catongo genotype displays defense mechanisms that include the synthesis of some defense molecules but without success in regards to elimination of the fungus. This phase is followed by the activation of protein metabolism which is achieved with the production of proteasome associated with autophagy as a precursor mechanism of PCD. This work also identifies candidate genes for further functional studies and for genetic mapping and marker assisted selection.